EFEKTIVITAS KERJA PT ACE HARDWARE DI PENGARUHI OLEH LINGKUNGAN KERJA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Raquelita Ruspanah; Eddy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
The research objective to be achieved is to determine the influence of the work environment on employee work effectiveness at PT. Ace Hardware Kelapa Gading through work motivation. This research uses quantitative methods. The population in this study were employees of PT. Ace Hardware Kelapa Gading. The technique used for sampling is a saturated sample, all members of the population are sampled. The data analysis method uses path analysis. The research results can be concluded as follows: 1). The work environment has a direct and significant effect on employee work effectiveness. 2). Work motivation has a significant direct effect on employee work effectiveness. 3). The work environment has a significant direct effect on work motivation. 4). The work environment does not have a positive and significant indirect effect on work environment on employee at PT. Ace Hardware Kelapa Gading through work motivation.